OBJEKTIVITAS BERITA SIMPOSIUM TRAGEDI 1965 (Analisis Isi Berita Simposium Tragedi 1965 dalam media Online CNN Indonesia pada 18-19 April 2016) - Masnugraheni, Dwiagata; Amanda Gelgel, Ni Made Ras; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2018)
ABSTRACT The media continues to innovate and generate new findings, one is a conventional newspaper currently has become the online news portal. These developments make the information very easily to be spread and become faster. However, the media need to know what should be done or not to reach an ideality media refers to normative media. CNNindonesia.com on the April, 18- 19 2016 intensively preaching the symposium that was first held for discussing violations of human rights in 1965. In the intensive period, CNNIndonesia.com published 21 news with two live news, about over a range time was not less than 3 hours. This study aimed to understand the objectivity of symposium 1965 on news portal online at CNN Indonesia period 18-19 April 2016. The research was used quantitative approach with the method of contents analysis. The result of this research, the objectivity of news portal online CNNindonesicom showed factuality (factual, accuracy, complete, and relevant) quite a high level of, but from the impartiality (access proportional, two sides, non evaluative, and non sensational) showed the lower value. Keywords: Contents Analysis, Objectivity, Online News, Tragedy of 1965